Discipline survival kit for the secondary teacher - Thompson, Julia G. (West Nyack, N.Y. : Center for Applied Research in Education, 1998)
The discipline dilemma: crowd control or self-discipline? Getting ready to make a good impression. Door to door: using class time wisely. A partnership approach to discipline. Preventing discipline problems. Dealing with problems once they occur. Strategies for solving specific problems...
Keywords: Education; Classroom management; Secondary education; Teacher-student relationships; Teacher effectiveness; Education, Secondary; Teacher effectiveness; Teacher-student relationships; Classroom management